Unique Anomalous Origin of the Left Anterior Cerebral Artery - Burbank, Nicole S.; Morris, P. Pearse (American Journal of Neuroradiology, 2005)
Summary: We present the case of an anomalous origin of the left anterior cerebral artery (ACA) from the supraclinoid segment of the right internal carotid artery. Because of improved imaging quality, anomalies of the ACA–anterior communicating artery (AComA) complex are increasingly recognized on transaxial images. Although most of these anomalies are incidental findings of little clinical significance, some ACA-AComA complex anomalies are clinically significant. Recognition of these anomalies may be instrumental in developing a differential diagnosis or for improved surgical planning.